Structural single and multiple crack detection in cantilever beams using a hybrid Cuckoo-Nelder-Mead optimization method. (15th January 2018) - Moezi, Seyed Alireza; Zakeri, Ehsan; Zare, Amin
Highlights: Modelling cracks using Euler-Bernoulli theory and Transfer Matrix Method (TMM). Proposing a method for estimating single/multiple crack(s) in multi-step beam. Using COA-NM method for estimating the crack and comparing with other methods. Higher accuracy in estimating cracks and lesser number of function evaluations. Validating the results by experimental modal tests on a single-cracked beam. Abstract: In this study, the number, location and depth of cracks created in several Euler-Bernoulli beams, such as a simple beam and a more complex multi-step beam are investigated. The location and depth of the created cracks are determined using the hybrid Cuckoo-Nelder-Mead Optimization Algorithm (COA-NM) with high accuracy. The natural frequencies of the cracked beams are determined by solving frequency response equations, and performing modal test experiments. Results of COA-NM show a higher accuracy and convergence speed compared with other methods such as GA-NM, PSO-NM, GA, PSO, COA and several previous studies. Amount of calculations performed by COA-NM to achieve this accuracy is much less compared to other methods.